Integrated Application of Health Information Technology in Chronic Disease Management - Zhuolin Yi (Innovation in Science and Technology, 2024)
The prevalence of chronic diseases is a critical challenge for healthcare systems worldwide. This study evaluates the integration of Health Information Technology (HIT) in managing chronic conditions, focusing on Electronic Health Records (EHRs), Mobile Health Monitoring, and Personalized Interventions. We aim to assess the impact of HIT on patient self-management, clinical effectiveness, and quality of life, offering insights for healthcare providers and policymakers.